2018
DOI: 10.7566/jpsj.87.083704
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Layered Oxychalcogenide La2O2Bi3AgS6

Abstract: Recently, we reported the observation of superconductivity at ~0.5 K in a La2O2M4S6-type (M: metal) layered oxychalcogenide La2O2Bi3AgS6, which is a layered compound related to the BiS2-based superconductor system but possesses a thicker Bi3AgS6-type conducting layer. In this study, we have developed the La2O2Bi3AgS6-type materials by element substitutions to increase the transition temperature (Tc) and to induce bulk nature of superconductivity. A resistivity anomaly observed at 180 K in La2O2Bi3AgS6 was syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…Later on, the metal (M) site of La 2 O 2 M 4 S 6 has been modified as M = Bi 3 Ag, and the resultant compound was La 2 O 2 Bi 3 AgS 6 [51] . This newly designed oxychalcogenide La 2 O 2 Bi 3 AgS 6 showed metallic conductivity and superconductivity at T c = 0.5 K [52]. Previous studies on the two-layer-type (BiS 2 -based LnO 1−x F x BiS 2 ) phase has suggested that the doping effect at the various sites of a compound induced bulk superconductivity or improve the superconducting properties [68][69][70][71][72], which has been understood by in-plane chemical pressure effects.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Later on, the metal (M) site of La 2 O 2 M 4 S 6 has been modified as M = Bi 3 Ag, and the resultant compound was La 2 O 2 Bi 3 AgS 6 [51] . This newly designed oxychalcogenide La 2 O 2 Bi 3 AgS 6 showed metallic conductivity and superconductivity at T c = 0.5 K [52]. Previous studies on the two-layer-type (BiS 2 -based LnO 1−x F x BiS 2 ) phase has suggested that the doping effect at the various sites of a compound induced bulk superconductivity or improve the superconducting properties [68][69][70][71][72], which has been understood by in-plane chemical pressure effects.…”
Section: Introductionmentioning
confidence: 85%
“…The single crystals of LnO 1−x F x BiS 2 can be easily exfoliated (layer by layer) because of the plate-like shape and the existence of a van der Waals gap between the BiS planes [46][47][48]. Notably, the van der Waals gap between two BiS planes became the essential feature when designing four-layer-type La 2 O 2 M 4 S 6 (M: metals) compounds [49][50][51][52], which is the central issue of this review article. The concept of designing new BiS2-based compounds with a thicker (four-layer-type) superconducting layer can be related to the case of the high-Tc cuprates [1,[53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest Tc up to 11 K was observed in a high-pressure phase of LaO1-xFxBiS2 [12][13][14][15][16]. Recently, we reported superconductivity in the oxychalcogenide La2O2Bi3AgS6 with Tc of 0.5 K [17]. Furthermore, we reported that Tc can be increased up to 2.4 K by Tin (Sn) substitution at the silver (Ag) site of La2O2Bi3AgS6 [18].…”
Section: Introductionmentioning
confidence: 99%